2016
DOI: 10.1038/ncomms11132
|View full text |Cite
|
Sign up to set email alerts
|

Gate-controlled electromechanical backaction induced by a quantum dot

Abstract: Semiconductor-based quantum structures integrated into mechanical resonators have emerged as a unique platform for generating entanglement between macroscopic phononic and mesocopic electronic degrees of freedom. A key challenge to realizing this is the ability to create and control the coupling between two vastly dissimilar systems. Here, such coupling is demonstrated in a hybrid device composed of a gate-defined quantum dot integrated into a piezoelectricity-based mechanical resonator enabling milli-Kelvin p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 35 publications
(53 reference statements)
1
47
0
Order By: Relevance
“…1 ). Figure 1b details the motional piezovoltage V d measured at different actuation voltages V a , showing a resonance peak which corresponds to the fundamental flexural mode 39 , 40 with frequency ω M /2 π = 1.716 MHz and quality factor Q = 5 × 10 4 . With increasing V a , the mechanical amplitude is deformed into a sawtooth-shape reflecting the emergence of a nonlinearity in the underlying harmonic potential 41 .…”
Section: Resultsmentioning
confidence: 99%
“…1 ). Figure 1b details the motional piezovoltage V d measured at different actuation voltages V a , showing a resonance peak which corresponds to the fundamental flexural mode 39 , 40 with frequency ω M /2 π = 1.716 MHz and quality factor Q = 5 × 10 4 . With increasing V a , the mechanical amplitude is deformed into a sawtooth-shape reflecting the emergence of a nonlinearity in the underlying harmonic potential 41 .…”
Section: Resultsmentioning
confidence: 99%
“…However, the key to achieving these objectives is the dual requirement of low phonon numbers and the ability to resolve them with low back-action [38]. Recent work has shown that these pre-requisites are now within reach to this architecture with phonon numbers below 1000 and a resolution of 70 phonons being observed [39].…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Stress-induced performance change of the CdS nanocrystals has been reported in [20]. Semiconductor QDs have been embedded in electromechanical resonators in reference [21]. It was stated that the wavelength tuneability becomes a fundamental requirement for a number of new applications [22], which promotes the research and development in integrating QDs with electromechanical devices.…”
Section: Introductionmentioning
confidence: 99%